Time-optimal control of a solid-state spin amidst dynamical quantum wind - Yang Dong; Wang Jiang; Xue-Dong Gao; Cui Yu; Yong Liu; Shao-Chun Zhang; Xiang-Dong Chen; Ibério de P. R. Moreira; Josep Maria Bofill; Gael Sentís; Ramón Ramos; Guillermo Albareda; et al. (npj Quantum Information)
Abstract Time-optimal control holds promise across the full spectrum of quantum technologies, where the rapid generation of unitary gates and state transformations is crucial to mitigate decoherence effects. In practical scenarios, quantum systems are always immersed in an external time-dependent field or potential, either owing to the inevitable influence of the environment or as a sought-after effect for enhanced coherence. The challenge then lies in finding the time-optimal approach to navigate quantum systems amidst dynamical ambient Hamiltonians, a pursuit that has proven elusive thus far. We showcase the implementation of arbitrary quantum state transformations and a universal set of single-qubit gates under a background Landau-Zener Hamiltonian. Leveraging the favorable coherence properties of timedomain Rabi oscillations, we achieve velocities surpassing the Mandelstam-Tamm quantum speed limit and significantly lower energy costs than those incurred by conventional quantum control techniques. These findings highlight a promising pathway to expedite and economize high-fidelity quantum operations.